Future Development of Renewable Energy in Russia: A Case of Solar Power - Rausser, Gordon; Chebotareva, Galina; Smutka, Luboš; Strielkowski, Wadim; Shiryaeva, Julia (Frontiers in Energy Research, 2022)
Currently, there is a growing number of studies related to assessing the cost-effectiveness of renewable energy projects around the world. This topic is also very relevant for the Russian energy market that is otherwise dominated by oil and gas. The Russian Ministry of Energy forecasts that local power plants running on the renewable energy sources (RES) may not become economically efficient until 2025 or later. However, a research question arises: Is it possible to effectively implement RES projects in Russia without any state support? In order to answer this question, the authors need to assess the economic feasibility of seven scenarios for the construction of a solar power plant in the Orenburg region of Russia. The methodological basis of this work is the widely used in the energy sector classic method of investment analysis based on the calculation of discounted indicators: net present value (NPV), payback period (DPP) and internal rate of return (IRR) of the project. All our calculations are based on industry-specific initial capital investment estimates, energy storage equipment costs, and related annual operating costs. This led to the development of the scenarios on the basis of an analysis of the features of electricity and capacity generation in the Orenburg region, the existing options for joining the trading system of the energy market, energy storage applications, as well as the availability of the Russian government support and funding for the solar energy projects. Our results demonstrate that the economic feasibility of the development of renewable energy in Russia can become a reality. Out of the seven scenarios, three yielded the positive economic outcome (among them there were the two project scenarios without government support). These two projects featured the sale of electricity in retail markets and the installation of an additional energy storage system, despite an almost twofold increase in capital investments. The projects in question achieved the best economic results according to the three calculated criteria. In particular, the scenario that provided for the work on the retail market directly to the energy consumer receives an NPV of more than 1.5 times higher than other projects, an IRR of 10% and pays off at least 3 years faster. Achieving a positive economic result in the wholesale market was possible only in case of state support for the project. In addition, this scenario of the project numerically reached almost identical indicators, as in the case of selling energy on the retail market in the region where the power facility operates: NPV is almost 127 million rubles, IRR is within 13.9%, and DPP is 15 years. Other scenarios that do not provide for the use of energy storage systems or do not have state support for working in the wholesale market are not self-sustaining even during the 25-year life of energy equipment. These results might have practical significance and will be used in developing an approach to creating a profile of regions in terms of the advancements of renewable energy, as well as in developing strategies for the incentives of this sector in Russia.